Optimalisasi Media Whatsapp Dalam Komunikasi Organisasi Sekaa Truna Truni (STT) Sastra Emas - I Wayan Sutama; I Gede Putra (Pasupati, 2022)
Youth organizations have a position and an important role for the sustainability of social life of people's culture.The current media development of communication is a good opportunity at improving youth productivity and creativity within the organization. This writing aims to describe how media optimization of whatapp groups in improving sradha bhakti members of the organization. By using a qualitative descriptive approach, Data gathering is done with observation, An interview, and documentation.The research shows communication of the organization truna-truni (STT) gold literature in increasing sradha and bhakti through five stages: research, planning, execution, evaluation, and reporting. Communication using media organization whatapps group to develop effective communication among members and member of the organization in running of a wheel. That has not communication were caused by several obstacles which includes technical obstacles, the semantic relation, human and obstacles. Necessary engineering communication that the dynamic can move, sustainable, and moving according to prinsip-prinsip organization.Engineering communication covering 1. interaction and personal communications among members of intensive and solid, 2. establishes the identity of the organization and common aims in the structure, 3. minimize potential difference or disagreement, 4. visionary leadership, 5. developed a style of personal relationships among members effectively, and 6. run principle leadership the relevant organisations, openness, honesty, accountability, and cooperation.